Umbilical cord blood TSH level: correlation with congenital hypothyroidism - Jillela, Mahesh Reddy; Reddy Keshireddy, Padmaja; Goli, Seshagiri; Chiluka, Archana; Chitgope, Ramya (International Journal of Contemporary Pediatrics, 2021)
Background: Congenital hypothyroidism is the most common preventable cause of mental retardation. Screening methods include measuring cord blood and venous blood TSH level. The objective of this study was to determine the impact if any of various risk factors affecting these levels. Methods: It was a cross sectional study done at our hospital and 263 cord blood samples were collected and TSH levels measured. The variables included in the study are parity of mother, GDM, mode of delivery, birth weight, gestational age, sex, weight appropriate for gestation, Apgar score. Results: In our study 35 among 263 cord blood samples were found to have CB TSH levels above the cut off value of 20 mIU/l and repeat venous sampling done on fifth day of life showed only one sample had high TSH with low free T4 levels and remaining 34 samples showed TSH levels which were significantly down from the earlier peak. The p value, ROC curve, test of significance and criterion cut off levels were made for each of the variables mentioned above. Among the variables studied, mode of delivery (<0.001), gestational age (p=0.001), low Apgar score (p=0.001) had p values which were statistically significant. Conclusions: Incidence of congenital hypothyroidism in our study is 0.0038%. There was no sexual predilection and the high cord blood TSH levels may be due to perinatal stress factors such as emergency LSCS, low Apgar score and prematurity which had significant positive correlation as evidenced with p values (≤0.001).